A sequence of flaps and dissection exercises in the living model to improve the learning curve for perforator flap surgery. (December 2020) - Pignatti, Marco; Tos, Pierluigi; Garusi, Cristina; Schonauer, Fabrizio; Cherubino, Mario; Tiengo, Cesare; Ciclamini, Davide; Cozzolino, Santolo; Di Maro, Eva; Jiga, Lucian P.; Ionac, Mihai; Nistor, Alexandru; et al.
Highlights: Perforator flap surgery can be successfully taught in living tissues, whose quality is optimal and difficulties are similar to the ones in humans. We describe a sequence of perforator flaps and dissection exercises that can be performed in pigs. This sequence includes previously described techniques and new ones that reproduce clinical situations in humans. The sequence can be successfully performed, during a course, by students not trained in perforator flap surgery. Abstract: Introduction: The training to learn how to perform perforator flaps requires practice on a living model to optimize dissection and to evaluate outcome. The purpose of this study was to describe a training model that optimizes the use of animals in order to perform the maximum number of exercises per animal. Material and methods: The sequence has been planned and practiced by the first and last author, recorded perfected and implemented in a two-day surgical course. The sequence was then evaluated by the trainers and the trainees by means of a questionnaire. Results: All students were able to complete the sequence of exercises before the end of the second day except two (8/10) who could not complete one exercise each. The students considered the Deep Superior Epigastric Artery Perforator flap the most difficult to perform, being the most technically demanding. The sequence of exercises was judged either easily reproducible or reproducible by all the students. Two students suggested to postpone the DSEAP flap to the second day, after some training, to optimize the experience with the most challenging and rewarding flap. Conclusions: The training sequence proposed offers a wide range of exercises and allows four trainees, divided in two teams, to work and learn on the same animal. They can perform a wide range of flaps and also harvest the internal mammary vessels. The living model allows for evaluation of the quality of the surgical performance, judged by the difficulties and complications encountered during dissection, and finally through the feedback of flap perfusion.